Integrated Pancasila Values-Based Economic Character Strengthening Program - Agussalim Agussalim; Arsad Arsad; Fitriani Fitriani; Fadilah Try Mursyid; Evi Adriani; Zuhri Saputra Hutabarat (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study investigates a novel approach to counter radicalism in educational settings through the implementation of the Integrated Pancasila Values-Based Economic Character Strengthening Program. The aim of this study is to evaluate the effectiveness of the program, which is designed to prevent radicalism by enhancing students' understanding and attitudes towards Pancasila's economic principles. This action research involved planning, implementation, observation, and reflection phases to assess the program. The research subjects included ninety-two students from the Economic Education Study Program at Nggusuwaru University (Unswa) Bima. Data collection during the study phases was conducted using observation sheets, questionnaires, and situational judgment assessments. The data were analyzed through quantitative descriptive analysis. The findings underscore the potential of values-based education initiatives to cultivate essential civic virtues in diverse learning environments. In conclusion, the program demonstrated significant efficacy in fostering a deeper comprehension and appreciation of Pancasila's economic principles, suggesting a viable strategy for mitigating radicalism through educational interventions.